Mineral Mudah Lapuk Material Piroklastik Merapi dan Potensi Keharaannya Bagi Tanaman - Aini, Lis Noer; Mulyono, Mulyono; Hanudin, Eko (Universitas Muhammadiyah Yogyakarta, 2016)
The eruption of Mount Merapi had been giving adverse effect for the community, but on the other hand, there are great benefits in it such as the enrichment back to the land. Enrichment process in land with materials that are rich in nutrients is often known as rejuvenation. In general, the rocks containing certain minerals or mineral assemblages, which has large amount of the potential nutrient that can be used by plants in the form of weathered minerals. Therefore, it is a big question about the relationship between primer mineral deposits on Mount Merapi volcanic material with the potential nutrient for crop. The results showed that the identification of Merapi pyroclastic material derived from basaltic andesite magma with primary mineral content easily weathered the dominant form of plagioclase. Utilization of volcanic material as macromineral is easy to use, because the nutrient content of the existing potential in minerals included in the group of minerals that easily weathered.